Inter-relationship between footprints and photogrammetry - Cunha, Francisco Valmor Macedo; Rodrigues, Tárik Augusto Amorim; Alves, Jonas Almeida; Santos, Jean Douglas Moura; Martins, Maria do Carmo Carvalho (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Alterations in foot landing position have often been associated with the appearance of deformities in lower limbs. However, there are no studies that prove the relationship between these two variables in healthy individuals. Objective: To investigate the relation between changes in feet and lower limbs by plantigraphy and computerized photogrammetry. Methods: The study included 70 young adults, 42 women (height: 1.60±0.01 m; body weight: 58.0±0.92 kg; body mass index: 22.0±0.31 kg/m2 ) and 28 men (height: 1.70±0.01 m; body weight: 70.0±1.4 kg; body mass index: 23.0±0.42 kg/m2 ) with mean age of 21.62±2.0 and 22.18±2.09 years, respectively. Plantigraphy of both feet and photographic capture in the anterior frontal plane of lower limbs and foot, posterior frontal of the tendon of the calcaneus and in the sagittal plane of lower limbs were performed. Results: A strong positive correlation was observed between the Chippaux-Smirak and the Staheli indexes (Men– r: 0.863 and p<0.001; Women– r: 0.973 and p<0.001) and a weak positive correlation between the malleolar angle and the Cavanagh-Rodgers index (Men– r: 0.386 and p 0.003; Women– r: 0.280 and p 0.010). Conclusion: There was no correlation between footprint indexes and lower limb angles measured by computerized photogrammetry.